Correlation Between Starch Damage, Alveograph Parameters, Water Absorption and Gelatinization Enthalpy in Flours Obtained by Industrial Milling of Argentinian Wheats - Jovanovich, Germán (2003)
Flours obtained by industrial milling of different argentinian wheats, including flour 000, flour 0000, different milling fractions, and flour obtained with a Bühler mill, were utilized to correlate the farinograph and alveograph parameters and the enthalpy of starch gelatinization, with the starch damage. In some cases, the same wheat sample was milled with different roll pressure, in order to obtain different levels of starch damage with the same wheat. The degree of starch damage affected the water absorption, the parameters P and P/L of the alveograph, and the enthalpy of starch gelatinization. The enthalpy of starch gelatinization correlates better with starch damage when differences in the degree of damaged starch are the result of applying a different pressure of the roll during milling. The parameter P/L seems to be the most sensible to reflect the different roll pressure during milling.